A novel oxidative stress marker in patients with Alzheimer's disease: dynamic thiol–disulphide homeostasis. Issue 6 (4th April 2016) - Gumusyayla, Sadiye; Vural, Gonul; Bektas, Hesna; Deniz, Orhan; Neselioglu, Salim; Erel, Ozcan
Abstract : Objective: The aim of this study was to evaluate the dynamic thiol–disulphide homeostasis as an oxidative stress parameter, using a newly proposed method, in patients with Alzheimer's disease. Methods: In total, 97 participants were included in the study. Among them, 51 had been diagnosed with Alzheimer's disease, and the remaining 46 were healthy individuals. Total thiol (–SH+–S–S–) levels and native thiol (–SH) levels in serum of each participant were measured. The amount of dynamic disulphide bonds (–S–S–) and (–S–S–) ×100/(–SH), (–S–S–) ×100/(–SH+–S–S–), and –SH×100/(–SH+–S–S–) ratios were calculated from these values. The obtained data were used to compare Alzheimer's disease patients with healthy individuals. Results: The average total thiol and native thiol levels of patient with Alzheimer's disease in the study were found to be significantly lower than those levels of healthy individuals. In addition, in the patient group, the –S–S–×100/–S–S+–SH ratio was found to be significantly higher, whereas the –SH×100/–S–S+–SH ratio was found to be significantly lower compared with healthy individuals. Total thiol and native thiol levels, dynamic disulphide bond amount, and –S–S–×100/–SH, –S–S–×100/–S–S+–SH, and –SH×100/–S–S+–SH ratios were not found to be correlated with mini mental state examination score or duration of disease. Conclusion: Recent studies have shown that oxidative stress is the one of the molecular changes underlying the pathogenesis of Alzheimer's disease. In this study, we have investigated the dynamic thiol–disulphide homeostasis in patients with Alzheimer's disease, using a novel method.